BS EN 16035. Hardware performance sheet (HPS). Identification and summary of test evidence to facilitate the inter-changeability of building hardware for application to fire resisting and/or smoke control doorsets and/or openable windows. (11th August 2022) - British Standards Institution,
No abstract available